2016
DOI: 10.1101/gad.277665.116
|View full text |Cite
|
Sign up to set email alerts
|

PolySUMOylation by Siz2 and Mms21 triggers relocation of DNA breaks to nuclear pores through the Slx5/Slx8 STUbL

Abstract: High-resolution imaging shows that persistent DNA damage in budding yeast localizes in distinct perinuclear foci for repair. The signals that trigger DNA double-strand break (DSB) relocation or determine their destination are unknown. We show here that DSB relocation to the nuclear envelope depends on SUMOylation mediated by the E3 ligases Siz2 and Mms21. In G1, a polySUMOylation signal deposited coordinately by Mms21 and Siz2 recruits the SUMO targeted ubiquitin ligase Slx5/Slx8 to persistent breaks. Both Slx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(170 citation statements)
references
References 67 publications
6
161
3
Order By: Relevance
“…Interestingly, polySUMOylation in G1 phase by Siz2 and Mms21 relocates persistent breaks at the nuclear pore in a Slx5/Slx8 dependent manner [82]. On the other hand, monoSUMOylation at S phase mediated by the SMC5/ 6-Mms21 E3 complex cause relocation of the breaks to the nuclear envelope protein Mps3 [82]. Similarly, it was shown that eroded telomeres also relocate to the nuclear pores in a SUMOylation dependent manner involving the function of the Slx5/Slx8 complex [83].…”
Section: Spatial Organization Of Dna Repair In the Nucleusmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, polySUMOylation in G1 phase by Siz2 and Mms21 relocates persistent breaks at the nuclear pore in a Slx5/Slx8 dependent manner [82]. On the other hand, monoSUMOylation at S phase mediated by the SMC5/ 6-Mms21 E3 complex cause relocation of the breaks to the nuclear envelope protein Mps3 [82]. Similarly, it was shown that eroded telomeres also relocate to the nuclear pores in a SUMOylation dependent manner involving the function of the Slx5/Slx8 complex [83].…”
Section: Spatial Organization Of Dna Repair In the Nucleusmentioning
confidence: 95%
“…Recent observations showed that persistent DSB relocation to the nuclear envelope also depends on SUMOylation mediated by the SUMO E3 ligases Siz2 and Mms21 [82]. Interestingly, polySUMOylation in G1 phase by Siz2 and Mms21 relocates persistent breaks at the nuclear pore in a Slx5/Slx8 dependent manner [82]. On the other hand, monoSUMOylation at S phase mediated by the SMC5/ 6-Mms21 E3 complex cause relocation of the breaks to the nuclear envelope protein Mps3 [82].…”
Section: Spatial Organization Of Dna Repair In the Nucleusmentioning
confidence: 97%
See 1 more Smart Citation
“…While the SUMO-ligase deficient cells are viable, in budding yeast, they are slow growing and display enhanced chromosome loss and breakage coupled with dependence on active DNA-damage signalling mediated by Mec1, the yeast homolog of the phosphatidyl inositol 3-kinase ATM (Ataxia telangiectasia mutated) protein [10]. Mms21 is required for resolution of X-shaped DNA intermediates at MMS-damaged replication forks [18] and relocation of DNA double strand breaks to the nuclear pore for repair [21]. Human MMS21/NSE2 (hMMS21 or NSMCE2) is relatively less characterized; it is also a SUMO ligase that sumoylates hSMC6 and the DNA repair protein TRAX and is required for DNA repair and prevention of DNA-damage induced apoptosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…2). 64,76,122 Their inter-dependence in DSB localization implicates both protein entities in recombinational repair and DSB tethering to the nuclear envelope 56,123 (Fig. 2).…”
Section: Roles Of Rtt107 When Partnered With Rtt101 Cullin Ubiquitin mentioning
confidence: 99%